Pengaruh Relative Advantage, Complexity, Compatibility, Trialability dan Observability terhadap adopsi Cloud accounting pada UMKM di Kecamtan Rambah. - Julia Rosadi; Fefti Yulian Mela; Nurhayati (Politeknik Raflesia Press, 2026)
Abstrak— The purpose of this study was to determine the influence of Relative Advantage, Complexity, Compatibility, Trialability, and Observability on cloud accounting adoption among MSMEs in Rambah District. This study used primary data collected directly from primary sources, namely respondents, thus the data were derived from direct field information acquisition.The method used was quantitative. The population in this study consisted of 6,884 MSMEs in Rambah District, while the sample size was 32 MSMEs. The sampling technique used was purposive sampling. The research variables were Cloud Accounting (Y), Relative Advantage (X1), Complexity (X2), Compatibility (X3), Trialability (X4), and Observability (X5). The analytical methods used were descriptive analysis, validity testing, reliability testing, classical assumption testing, multiple linear regression, coefficient of determination testing, and hypothesis testing using SPSS version 25. The results showed that Relative Advantage and Compatibility had a positive and significant effect on cloud accounting adoption. Meanwhile, Complexity, Trialability, and Observability do not significantly influence cloud accounting adoption.